PRINSIP HUKUM ISLAM DALAM BIDANG HUKUM KELUARGA - Husni Husni; Muhammad Yasir (SYARIAH: Journal of Islamic Law, 2021)
Islamic family law as an offer in solving several problems. In essence, it is not intended to teach Muslims so that later in marriage they can practice it, but the law here is solutive, meaning that Islamic law provides solutions in solving family problems that occur. This study aims to determine the principles of Islamic law in the field of family law. The results of this study show that Islamic family law is an offer in solving several problems. In essence, it is not intended to teach Muslims so that later in marriage they can practice it, but the law here is solutive, meaning that Islamic law provides solutions in solving family problems that occur.